Thermal aging behavior in Cu-Al-Ni-xCo shape memory alloys - Saud, Safaa Najah (Kluwer Academic Publishers, 2015)
effects of aging on the phase transformation temperatures, morphology, and mechanical properties were investigated in the Cu-Al-Ni-xCo (x = 0.4, 0.7, and 1.0 mass%) SMAs via differential scanning calorimetry, field emission scanning electron microscopy, X-ray diffraction, tensile, vickers microhardness, and shape memory effect test. The results show that the phase morphology and the presence of ? 2 precipitates in different sizes, volume fractions, and distributions have an obvious effect on the phase transformation characteristics and properties. In addition, a noticeable variation in the transformation temperatures and thermodynamic parameters were occurred with the aging. In tension, the highest tensile strength and tensile strain of 750 MPa and 5.5 % were indicated in the Cu-Al-Ni-1 mass% Co alloy after being aged at 523 K for 24 h and 373 K for 48 h, respectively. However, the results of the strain recovery by shape memory effect were varied in accordance with the variation of the ?1' and ß1' morphology and volume fraction of ? 2 precipitates. In aged alloy of 523 K for 48 h, the thickness of ?1' and ß1' phases and the volume fraction of ? 2 precipitates increase, thus, the movement of martensitic interfaces is restricted causing an increase in e t by SME.